Integrating Steam in English Language Classrooms (K1-K2) - Malika Yunusova Miralimovna (Researchparks Publishing, 2022)
The article deals with the issues based on integrating STEAM in English language classrooms. It is revealed that STEAM education is not a separate subject, it implies the integration of knowledge from different areas, thanks to which this kind of education can be used in teaching different subject areas. A key feature of this kind of education is the interaction of younger students in line with teamwork, in the process of learner's activities in the mode of creating and demonstrating projects. Thanks to project activities, students get the opportunity to activate the creative, emotional, creative component of their personality. All this becomes possible due to the interdisciplinary applied nature of STEAM education.